Grave of the fireflies [videorecording (DVD)] - Nosaka, Akiyuki, 1930-2015 (Collector's series (Central Park Media (Firm)), 2012)
As the Empire of the Sun crumbles upon itself and a rain of firebombs falls upon Japan, the final death march of a nation is echoed in millions of smaller tragedies. Seita and his younger sister Setsuko are two children born at the wrong time, in the wrong place, and now cast adrift in a world that lacks not the care to shelter them, but simply the resources. They are forced to fend for themselves in the aftermath of fires that swept entire cities from the face of the earth.